Developing a homogeneous texture dish by combining solid and liquid foodstuff matrices. (15th August 2022) - Hernández, Sergio; Ribes, Susana; Verdú, Samuel; Barat, José M.; Talens, Pau; Grau, Raúl
Abstract: A dish with a uniform texture was developed for people with a poor oral health problem: dysphagia. Its texture and color were studied, along with its consumption and cold storage with reheating. The dish was constituted by softening carrot and integrated into thickened soup. Carrot was softened by applying enzymes via freeze-thaw impregnation (FI). Soup was thickened by guar gum. The results indicate both components achieved a similar texture. Firmness and cohesiveness increased significantly as temperature dropped. Judges were unable to detect the presence or absence of carrot in the dish by a sensorial compression assay, but could detect color changes. These outcomes were also verified by a digital image analysis. The results demonstrate the feasibility of using FI treatment combined with enzymes to soften vegetables and subsequently incorporating them into thickened liquid foodstuff to develop safe, sensory-accepted and texture-modified products for specific populations. Highlights: Solid and liquid foodstuffs' textures were homogenized. Texture and color slightly change along its intake and cold storage with reheating. Safe and attractive texture-modified food for dysphagics was designed.